Understanding the extent of leaching of selected species from sludge-based carbon additive and composite panels - Lim, Jenson Zhi Hao (Nanyang Technological University, 2023)
This report investigates the use of sewage sludge ash, produced from the incineration of household and industrial waste in Singapore. As land is limited in Singapore, the sewage sludge ash is typically buried in the Semakau landfill after additional treatment to determine it is safe for burial. The objective is to repurpose the sewage sludge ash to form high-quality products and evaluate if the products is effective in stopping or limiting metallic elements into the environment. The sewage sludge ash can contain a high concentration of organic and inorganic elements which can reuse for different purposes. Their potential as useful materials for various applications, including building materials and fertilizers, has been studied extensively by many researchers. In this report, the impact of humidity on the leaching properties and effectiveness of composite materials made with these materials is not well understood. In this study, properties of the composite material were determined using Inductively Coupled Plasma (ICP), pH tester, Shimazu mechanical tester, Fourier transform infrared (FTIR) and a contact angle goniometer. The effectiveness of the composite material in limiting or preventing the leaching of metallic elements was evaluated according to BS EN 12457-1 and NEA standards.